THE INTEGRATION OF CORPUS INTO EFL SPEAKING INSTRUCTION: A STUDY OF LEARNER PERCEPTIONS - Şahin Kızıl, Aysel; Savran, Zehra (International Online Journal of Education and Teaching, 2018)
Recent years have shown a growing interest in using corpora in language instruction, enhancing data-driven learning (DDL) pedagogy by promoting the use of tools and techniques of corpus linguistics in language classrooms. Many studies have tested the impact of corpus tools in EFL writing or vocabulary instruction; however, little attention has been paid to the integration of corpus tools into EFL speaking instruction. This paper describes a small-scale study of corpus use in enhancing English speaking performance of EFL learners with a focus on their perceptions towards web-based concordancing. Drawn in accordance with convenience sampling procedures, the participants of the study were 31 university level EFL learners who experienced DDL activities in the speaking classroom. Data collected through a post-instruction perception questionnaire were analysed using descriptive statistics. Results indicated that students benefited from concordance based learning activities, and also hold positive attitudes towards using it in learning speaking. The findings also point out some challenges to overcome while using web-based concordancing in EFL instruction. Keywords: EFL learners, data-driven learning (DDL), web-based concordancing, learner perceptions, speaking